2021
DOI: 10.15562/bmj.v10i3.2868
|View full text |Cite
|
Sign up to set email alerts
|

Mother's nutritional knowledge and behavior to stunting prevalence among children under two years old: case-control

Abstract: Introduction: Stunting among children still becomes a public health problem that needs serious attention. Stunting often occurs in 1000 days of a child's life. Some factors often cause stunting, such as lack of knowledge and nutrition for children. Aim to study the correlation between mother's nutritional knowledge and behavior in providing nutrition for children under two years old and the prevalence of stunting in Banteran Village, Sumbang District.Methods: This study is an analytical observational study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
2
0
4
Order By: Relevance
“…That is, a mother with a higher level of education is associated with better childcare practices. Studies have also found that knowledge of these things strongly predicts stunting in children under five years [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, a mother with a higher level of education is associated with better childcare practices. Studies have also found that knowledge of these things strongly predicts stunting in children under five years [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tinjauan scoping review ini didapatkan 11 studi yang membahas terkait hubungan pengetahuan gizi ibu terhadap kejadian stunting. Sembilan penelitian mengindikasikan adanya korelasi antara pengetahuan gizi ibu dan kejadian stunting 13,16,17,19,20,21,22,23,24 . Sedangkan sebanyak dua penelitian mengindikasikan tidak ada korelasi antara pengetahuan gizi ibu terhadap stunting 14,15 .…”
Section: Hubungan Pengetahuan Gizi Ibu Terhadap Kejadian Stuntingunclassified
“…et al (2021) menunjukkan bahwa terdapat hubungan antara tingkat pengetahuan gizi ibu dengan prevalensi stunting. Ibu dengan tingkat pengetahuan gizi yang kurang memiliki peluang 0,246 kali memiliki anak dengan risiko stunting pada anak dibandingkan responden dengan tingkat pengetahuan gizi yang baik 20 .…”
Section: Hubungan Pengetahuan Gizi Ibu Terhadap Kejadian Stuntingunclassified
See 1 more Smart Citation
“…Walaupun telah ada penurunan jumlah kasus secara umum, penurunan ini belum cukup berarti, dengan Asia, Asia Selatan, dan Sub-Sahara Afrika mencatatkan proporsi tertinggi (1,2). Studi mengenai kondisi gizi di Indonesia mengindikasikan adanya penurunan dalam angka prevalensi stunting, yaitu sekitar 26,92% pada tahun 2020 dan 24,4% pada tahun 2021.…”
Section: Pendahuluanunclassified